2014
DOI: 10.1016/j.livsci.2014.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salix babylonica and Leucaena leucocephala leaf extracts on ruminal fermentation characteristics, urinary purine derivative excretion and microbial protein synthesis of lambs

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…In contrast, Hernandez et al. () found that oral administration of Leucaena leucocephala extracts at 30 ml/d to lambs for 63 days had minor effects on ruminal fermentation, urinary purine derivative excretion and microbial protein synthesis.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, Hernandez et al. () found that oral administration of Leucaena leucocephala extracts at 30 ml/d to lambs for 63 days had minor effects on ruminal fermentation, urinary purine derivative excretion and microbial protein synthesis.…”
Section: Resultsmentioning
confidence: 93%
“…Hence, reducing protozoal populations could improve dietary N utilization and increase microbial protein synthesis flow to the intestine (Wang et al, 2012). In contrast, Hernandez et al (2014) found that oral administration of Leucaena leucocephala extracts at 30 ml/d to lambs for 63 days had minor effects on ruminal fermentation, urinary purine derivative excretion and microbial protein synthesis.…”
Section: Nitrogen Utilization and Efficiency Of Microbial Protein Synmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, tannins have been suggested to be suitable feed additives towards improving the digestive utilization of dietary protein (Hernandez et al, 2014;Salem et al, 2014). Nevertheless, tannins may also cause negative effects like reduction of ruminal degradation of organic matter (OM) or decreasing fiber and dry matter (DM) digestion when supplied at 30 rather than at 10 and 20 g tannins/kg DM (Al-Dobaib, 2009;Ammar et al, 2011;Salem et al, 2013).…”
mentioning
confidence: 99%
“…Several of those species contain secondary metabolites such as condensed tannins (CT), which are found in foliages, fruits and cortex; and when they are consumed by ruminants, form chemical complexes with proteins and carbohydrates, which reduce rumen degradation of those components (Ramirez‐Restrepo et al., ) and favours the passage of undegraded (‘bypass’) protein and the absorption of amino acids from the small intestine (Soltan et al., ). In addition, CT may increase microbial protein synthesis (Anantosook et al., ; Hernandez et al., ), increase nitrogen retention, reduce emissions of N 2 O from urine and reduce fermentation of fiber (Barry and Manley, ; Soltan et al., ).…”
Section: Introductionmentioning
confidence: 99%